Effect of Combined Hot Air, Heat Pump and Microwave Assisted Drying on Quality Characteristics of Onion Shreds - Sahoo, N. R.; Pal, U. S.; Dash, S. K.; Panda, M. K.; Sahoo, D. (Journal of Agricultural Engineering, 2014)
Onion shreds of 2 mm thickness were dried in convective hot air dryer (HAD) at 60°C (28 ± 4% R.H.), heat pump dryer (HPD) at 50°C (15 ± 2% R.H.) and microwave assisted convective dryer (MWD) at 240 W power and 500C individually and with combinations of drying methods. Drying times were observed to be 300, 360 and 75 min for lowering the moisture content of onion shreds from 675.8% to 6±1% (g/g dry matter) in HAD, HPD and MWD. In combination drying, application of MWD for completing drying after HAD or HPD reduced the drying time significantly, but there was higher discolouration of the products. Total drying time for HPD(50°C)-HAD(60°C) combination was lower with higher overall drying rate as compared to HAD(60°C)-HPD(50°C) drying. HAD(60°C)- HPD(50°C) combination drying yielded products of better colour, whereas the retention of pyruvic and ascorbic acids was higher in HPD(50°C)-HAD(60°C) drying method.